Exploring quantum discord. - Chong, You Quan. (2011)
Entanglement has always been regarded as a useful resource for pure state computation. In spite of substantial progress, the precise role of entanglement in quantum information processing remains an open question. More specifically, it was shown that entanglement may not be essential for a mixed state computational model called "Determnistic Quantum Computation with one quantum bit" (DQC1). This was subsequently demonstrated experimentally by Lanyon et al. It turns out that a useful measure to characterise correlations in such a model is the quantum discord, which attempts to capture quantum correlations in a bipartite system.